The use of Instagram by gastronomic influencers: Similarities and differences between instagramers concerned about healthy eating and foodies - Navarro-Beltrá, Marián; Herrero Ruiz, Laura (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The wide use of social networks by the population has led to the emergence of influencers. Within the gastronomy sector there are two types of digital opinion leaders: foodies and those concerned with healthy food. To compare the communication that these two profiles types carry out on Instagram, a content analysis of 339 publications made by the most important gastronomic instagramers in Spain is performed. The results show that their communication strategies differ and that the followers of the healthy profiles are the most active and interactive ones.